EXAMINING THE COST OF QUALITY IN THE CALCULATION OF COST OF GOODS OF PRODUCTION OF PALOLO DISTINCTIVE BROWN SUGAR - Ridwan, Ridwan; Ni Made Suwitri Parwati; Ansar, Muhammad; Halwi, Muh. Darma; Indriasari, Rahayu; Samir, Yulia Gita (Accounting Studies and Tax Journal (COUNT), 2024)
This study aims to find the concept of quality cost in calculating the cost of goods of typical Palolo brown sugar products in Palolo District, Sigi Biromaru Regency. This research is a qualitative study using an ethnomethodological approach. The research found four groupings in determining the COGS of brown sugar, namely Raw Material Costs, Support Costs, Factory Overhead Costs, and Quality Costs-Prevention Costs. In the brown sugar production process, from four categories of quality costs, the new brown sugar artisans carry out preventive cost activities, which include brown sugar quality planning activities, controlling the production process, and evaluating the quality of brown sugar.